Struvite-phosphorus effects on greenhouse gas emissions and plant and soil response in a furrow-irrigated rice production system in eastern Arkansas - Della Lunga, Diego; Brye, Kristofor R.; Roberts, Trenton L.; Brye, Jonathan; Evans-White, Michelle; Henry, Christopher G.; Lessner, Daniel J.; Arel, Chandler (Frontiers in Climate, 2024)
Phosphorus (P) fertilizers with low water solubility, like struvite (MgNH4PO4·6H2O), have been identified to possibly reduce nutrient losses in furrow-irrigated cropping systems. However, there is a lack of research on the impacts of P and nitrogen (N) fertilization on greenhouse gas [GHG; i.e., methane (CH4), nitrous oxide (N2O), and carbon dioxide (CO2)] production in furrow-irrigated rice (Oryza sativa). The objective of this study was to evaluate the effects of electrochemically precipitated struvite (ECST), chemically precipitated struvite (CPST), triple superphosphate (TSP), diammonium phosphate (DAP), environmentally smart nitrogen (ESN), and an unamended control (CT) on GHG emissions, global warming potential (GWP), and plant and soil responses at the up-slope position of a furrow-irrigated rice field in east-central Arkansas. Seasonal CH4 and CO2 emissions did not differ (P > 0.05) among fertilizer treatments, while N2O emissions were greater (P = 0.02) from CT (i.e., 5.97 kg ha-1 season-1), which did not differ from ECST, and were lowest from ESN (1.50 kg ha-1 season-1), which did not differ from TSP, CPST, ECST, and DAP. Global warming potential was greatest (P < 0.05) from CT (1612 kg CO2 eq. ha-1 season-1), which did not differ from ECST, and was lowest from ESN (436 kg CO2 eq. ha-1 season-1), which did not differ from TSP, ECST, CPST, and DAP. The combination of numerically greater yield and lower N2O emissions from CPST and ESN suggested that slow-release fertilizers could constitute an effective mitigation tool to reduce GHG emissions, maintain production, and improve sustainability in furrow-irrigated rice systems.